22+3x=2(x+3)

Simple and best practice solution for 22+3x=2(x+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 22+3x=2(x+3) equation:


Simplifying
22 + 3x = 2(x + 3)

Reorder the terms:
22 + 3x = 2(3 + x)
22 + 3x = (3 * 2 + x * 2)
22 + 3x = (6 + 2x)

Solving
22 + 3x = 6 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
22 + 3x + -2x = 6 + 2x + -2x

Combine like terms: 3x + -2x = 1x
22 + 1x = 6 + 2x + -2x

Combine like terms: 2x + -2x = 0
22 + 1x = 6 + 0
22 + 1x = 6

Add '-22' to each side of the equation.
22 + -22 + 1x = 6 + -22

Combine like terms: 22 + -22 = 0
0 + 1x = 6 + -22
1x = 6 + -22

Combine like terms: 6 + -22 = -16
1x = -16

Divide each side by '1'.
x = -16

Simplifying
x = -16

See similar equations:

| -2y=-24+10x | | 25-7=18 | | 6-2(4x+1)=5x-2(2x+7) | | -5.2=m-6.8 | | -(x+7)=36 | | 5y+50-8= | | 19.6+n=24.62 | | -20=f/2 | | 2t^2-30t+0=0 | | X/-9=-14 | | 17=-6-6x-1 | | -10x-2(12-5x)=-24 | | abs(3x-5)=abs(4x-2) | | 8-(x*x+7)=-35 | | .22(x+6)=.2x+5.3 | | x/3-9/4=x/6-1/2 | | 5v^2-17v=-6 | | 1/x=4/12 | | 8a-12=4(a-5) | | 6n^2+31n+18=0 | | 70m^2-73m+20= | | 2(x-8)=9 | | -2/3x=28 | | Q=j+jet | | X+78=x+41 | | -8=-2z+-14 | | 5y-6y+y+36=6y+30-2y | | 2u+6v=9 | | -3/4x=8/16 | | (255/256)/n | | √5/81 | | 0.9*x=180 |

Equations solver categories